SCIENCE AND EDUCATION IN FORMATION OF «NEW ECONOMY» IN UKRAINE - Savelyev, Yevhen; Kuryliak, Vitalina (Journal of European Economy, 2018)
The article formulates the concept of radical change in the role of science and education in the Ukrainian society and the ways of employing this transformation as the basis for economic reformation. The authors design the Ukrainian pattern of the new economy, the competitive capacity of which to be ensured through development and utilization of knowledge in the spheres of material production and services. Ukraine must find its specific scientific and technological priorities, concentrate financial resources at ensuring global leadership in certain fields, and change its economic structure in consideration for national scientific achievements. Education and science must develop not only as an important social function of the state, but also as a successful domestic and global business.